A Specific Subset of Transient Receptor Potential Vanilloid-Type Channel Subunits in Caenorhabditis elegans Endocrine Cells Function as Mixed Heteromers to Promote Neurotransmitter Release - Jose, Antony M. (Copyright © 2007 by the Genetics Society of America, 2007)
Transient receptor potential (TRP) channel subunits form homotetramers that function in sensory transduction. Heteromeric channels also form, but their physiological subunit compositions and functions are largely unknown. We found a dominant-negative mutant of the C. elegans TRPV (vanilloid-type) subunit OCR-2 that apparently incorporates into and inactivates OCR-2 homomers as well as heteromers with the TRPV subunits OCR-1 and -4, resulting in a premature egg-laying defect. This defect is reproduced by knocking out all three OCR genes, but not by any single knockout. Thus a mixture of redundant heteromeric channels prevents premature egg laying. These channels, as well as the G-protein Gα(o), function in neuroendocrine cells to promote release of neurotransmitters that block egg laying until eggs filling the uterus deform the neuroendocrine cells. The TRPV channel OSM-9, previously suggested to be an obligate heteromeric partner of OCR-2 in sensory neurons, is expressed in the neuroendocrine cells but has no detectable role in egg laying. Our results identify a specific set of heteromeric TRPV channels that redundantly regulate neuroendocrine function and show that a subunit combination that functions in sensory neurons is also present in neuroendocrine cells but has no detectable function in these cells.